190 Evaluating the Management of Cephalic Arch Stenosis in A North London Hospital. (12th October 2021) - Hammad, A; Al Midani, A
Abstract: Aim: Brachiocephalic fistulas (BCFs) are the most commonly used arteriovenous fistulas (AVFs). They are commonly associated with cephalic arch stenosis (CAS), a leading cause of dysfunction and failure. The 2018 European Society of Vascular Surgery guidelines recommend the consideration of stent grafts for managing CAS. In this study, we sought to evaluate the management of CAS in a North London hospital. Method: We carried out a retrospective study of patients who had undergone a fistulogram/fistuloplasty for CAS between May 2014 and May 2020. We extracted demographic data, information about their access, and information regarding surgical management of CAS, from the patients' records on VitalData. We extracted data about recurrence of CAS from their Cerner records. Results: Seventy patients were included. 54.3% were still alive at the time of data collection. The average age of those still alive was 65.8±14.1 years. 78.6% had a left BCF. 66% had previous access. 4.29% underwent stenting for CAS. The rest had fistulopasties alone. 90% required multiple fistulopaslties (mean=3.44±1.51). Median interval between access creation and first fistuloplasty was 1.90 years. 34.3% of patients underwent surgical repair of their AVF. AVF failure rate was 34.3%. Median interval between access creation and failure was 3.05 years. Median interval between first fistuloplasty and access failure was 1.34 years. Conclusions: Our data demonstrate a high rate of access failure in patients with CAS treated at our centre. Few of our patients had stent grafts inserted. The majority had fistuloplasties without stenting, which was associated with a high recurrence rate.